Empowering Coastal Communities Through Sustainable Economy and Adoption of Financial Technology in Bira Beach, South Sulawesi - Gaffar, Andi Nurrahma; Muhajir, Muhammad Nur Alam; Mursyid; Ilham; Aqidah, Nur Ariani; Hamida; Ikram, Muhammad; Zam, Muhammad Fahmi Ilyasir (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
Bira Beach in South Sulawesi is a leading coastal tourism destination with strong potential for local economic growth through micro, small, and medium enterprises (MSMEs). However, many MSMEs still face challenges related to limited digital literacy, product innovation, and understanding of sustainable business management. This community service program was designed to enhance MSME competitiveness, promote sustainable business practices aligned with the Sustainable Development Goals (SDGs), improve digital literacy, and foster collaboration among entrepreneurs, academics, and local government. Using participatory collaborative and descriptive methods, the program implemented a series of workshops, mentoring sessions, and field visits focusing on financial technology adoption, creative product innovation, and sustainable creative economy training. The results show an increased understanding of sustainable business concepts, greater readiness to adopt financial technology such as QRIS and e-wallets, and enhanced digital marketing capabilities among MSME participants. The program also encouraged stronger cooperation between MSMEs and local stakeholders to support long-term independence and sustainable community-based economic development in the Bira Beach area.